In silico screening of natural compounds from Jatropha curcas (Euphorbiaceae, Linn) and Jatropha gossypifolia (Euphorbiaceae, Linn) against SARS-CoV2, a COVID-19 main protease, using molecular docking approach - Emmanuel Kitete Mulongo; Jason T Kilembe; Gedeon Ngiala Bongo; Koto-te-Nyiwa Ngbolua; Dorothée Tshilanda Dinangayi; Damien Sha Tshibey Tshibangu; Pius T Mpiana (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
SARS-Cov2, the COVID-19 main protease is set to be a good target for potential inhibitors especially from plants. 6LU7, the crystal structure of COVID-19 has been used for docking with natural compounds from Jatropha curcas and Jatropha gossypifolia. The following compounds identified within J. curcas have given good binding affinities than Azythromycin (control sample): 2-methyl anthraquinone, Curcusone D, Palmarumycin CP1, Apigenin, Jatropholone A, Jatropholone B, Spirocurcasone and Multidione. The best score is for Palmarumycin CP1 -8.2 Kcal/mol. All these compounds are R05 satisfied, good HIA scores and good pharmacokinetic properties. In J.gossypifolia, 2,24,25-Trihydroxylanosta-1,7-dien-3-one ; Cleomiscosin A, Citlalitrione, Gossypifan, Jatrophenone, Jatropholone A, Jatropholone B, Gadain, Gossypidien, Falodone and Gossypiline are having good binding affinities than Azythromycin (control sample). The best score is for Cleomiscosin A -8.2 Kcal/mol. All these compounds are R05 satisfied, good HIA scores and good pharmacokinetic properties. This study has shown anti-COVID-19 potential of these two plants.